Development of a Web-Based PKL-Hub Management Information System Using the Waterfall Method - Dimas Afrizal; Silvia Qurrotul Ain Salsabila; Jefri Setia Puput Tri; M Adamu Islam Mashuri (Universitas Negeri Surabaya, 2025)
The implementation of Praktik Kerja Lapangan (PKL) often encounters challenges in data management, including difficulties in locating partner companies and ineffective activity monitoring. This study aims to develop a web-based PKL management information system, named PKL-Hub, using the Waterfall method. The system was developed using HTML, CSS, JavaScript, PHP, and MySQL, and provides key features such as PKL location search, registration management, digital logbooks, activity monitoring, and partner-based assessment. Functional testing using the Black Box Testing method indicates that all system features operate according to the defined requirements. Therefore, PKL-Hub is able to improve administrative efficiency and coordination among students, faculty, and partner companies in PKL implementation.